2014
DOI: 10.1007/s00441-014-1830-z
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cell spheroids in fibrin hydrogels exhibit improved cell survival and potential for bone healing

Abstract: Mesenchymal stem cells (MSC) have great therapeutic potential for the repair of nonhealing bone defects due to their proliferative capacity, multilineage potential, trophic factor secretion, and lack of immunogenicity. However, a major barrier to the translation of cell-based therapies into clinical practice is ensuring their survival and function upon implantation into the defect site. We hypothesized that forming MSC into more physiologic 3-dimensional spheroids, rather than employing dissociated cells from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 50 publications
9
116
1
Order By: Relevance
“…We and others have demonstrated that MSCs exhibit increased overall function and improved survival when formed into three-dimensional spheroids [6][7][8][9]. Compared with an equal number of dissociated MSCs, 15 000 cell MSC spheroids exhibited similar caspase 3/7 activity yet secreted up to 100 times the amount of vascular endothelial growth factor.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We and others have demonstrated that MSCs exhibit increased overall function and improved survival when formed into three-dimensional spheroids [6][7][8][9]. Compared with an equal number of dissociated MSCs, 15 000 cell MSC spheroids exhibited similar caspase 3/7 activity yet secreted up to 100 times the amount of vascular endothelial growth factor.…”
Section: Introductionmentioning
confidence: 99%
“…MSC spheroids were formed using the hanging drop technique over 48 h with 15 000, 30 000 or 60 000 cells per 25 ml droplet [6]. This range was selected due to previous reports of resulting sizes below and above the diffusion limit of oxygen, known increases in trophic factor secretion, and to examine spheroids of similar sizes reported in the literature [9,20,21].…”
Section: Spheroid Formation and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Human colon Matrigel -rich in growth factors, signal factors for cell proliferation -expensive and animal derived PC-3M, PrCa, NCI-H600 [74], HepG2 [75], A235, B16F10 [76] agar -damage on cells by forces from gel formation inside the agar -excellent mechanical properties human foreskin dermal fibroblasts [77], cortical cell [78] alginate -rapid formation of hydrogel scaffolds -strong chemicals required to break hydrogel networks to harvest MCSs human fat-derived stromal vascular fraction cells [79], human colon cancer cells (HCT116) [80] fibrin -promoting cell attachment -high cell viability human mesenchymal stem cell [81], B16-F1…”
Section: Micro-mouldingmentioning
confidence: 99%